If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + 7 = 27 Reorder the terms: 7 + 5n = 27 Solving 7 + 5n = 27 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 5n = 27 + -7 Combine like terms: 7 + -7 = 0 0 + 5n = 27 + -7 5n = 27 + -7 Combine like terms: 27 + -7 = 20 5n = 20 Divide each side by '5'. n = 4 Simplifying n = 4
| (n-6)*2=4 | | (n-6)*10=70 | | 65=-4(5b+3) | | 108-3x=4x+17 | | 14-6x=6-8x | | 7(2y-3)=28 | | 8x^3+4x^2-34x+15=0 | | -3(4-2w)=10 | | 3(4-3s)=34 | | 3g+15=5g-3 | | 9x+23=3x+197 | | -3(4-2n)=19 | | -3(4-2)=19 | | 2x+3=2(2x+7) | | 5x+26=15x-64 | | x*x=x | | x+2x-3x+4x-5x=-5 | | 2x^2-4kx+k=0 | | 9x^4-3x^2+1= | | 3x*2+5x+3=0 | | 2(x+1)-(x+2)=3 | | 2(x+1)-(x-2)=3 | | 72-3x=6x+24 | | 25xsomthing=105 | | 0.25(2-x)=9 | | 3(2x+5)=29-x | | 21=0.3(3-4x) | | 21=0.3(3-4) | | 21=0.393-40 | | 65=5(4-3x) | | 4x^2-8x-5=-5 | | 0.5(4-2x)=24 |